Pathological infant cry analysis using wavelet packet transform and probabilistic neural network - Muthusamy, Hariharan; Sazali, Yaacob, Prof. Dr.; Saidatul Ardeenaawatie, Awang (Elsevier Ltd., 2011)
Link to publisher's homepage at http://www.elsevier.com/